ANALISIS HAMBATAN LITERASI SISWA DALAM PENERAPAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS III DI SDN 111/I MUARA BULIAN - Putri Patricia Novelina Purba; Shayla Naina Fikria; Sentia Fita Ama; Khoirunnisa; Silvina Noviyanti (STKIP Subang, 2026)
This study examines the literacy barriers faced by third-grade students in the implementation of the Problem Based Learning (PBL) model in Indonesian language learning at SDN 111/I Muara Bulian. The problem addressed in this research arises from the mismatch between the demands of PBL, which requires adequate reading and comprehension skills, and the diverse literacy abilities of students. This study aims to analyze the forms of literacy barriers experienced by students during the implementation of PBL. A qualitative descriptive approach was employed, with data collected through classroom observations and teacher interviews. The research subjects consisted of 11 students in class IIIB and one classroom teacher as a supporting informant. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal two main literacy barriers. First, students experience reading fluency difficulties (slow readers), which hinder the efficiency of learning time and disrupt the sequence of PBL activities. Second, students demonstrate low reading comprehension, as they struggle to understand and restate the content of texts, limiting their participation in problem-solving discussions. These two barriers are interconnected, forming a chain that negatively affects the effectiveness of PBL implementation. The study concludes that the success of PBL is not only determined by the teacher’s mastery of instructional strategies but also depends heavily on students’ foundational literacy skills. Therefore, structured literacy scaffolding is necessary prior to implementing PBL to ensure optimal learning outcomes